Assessment of Impact of Frontline Demonstrations in North Eastern-Hill Region of India - Parihar, A. K.; Dixit, G. P.; Gupta, S. (Indian Journal of Hill Farming, 2018)
Pulses are important components of balanced diet and playing key role in alleviating malnutrition and micronutrient deficiencies in third world countries. Among the pulses, lentil is recognised as nutritious pulse crop and grown in different agro-ecology of India. Several high yielding varieties have been developed in the past, however, only few of them could reach to the farmers field, particularly in NEH region. Frontline demonstration is the best established strategy to popularize the newly developed technology at farmer’s field. Therefore to assess the yield gap and impact of demonstration in North-eastern region present attempt has been made. The results revealed that there was more than 29 Percent increase in grain yield through demonstrations over the farmer’s practices being followed. Similarly, the average technology gap was 372 kg/ha which exhibited the feasibility of improved technology at the farmer’s field. The average technology index was 31% during the study period which is in accordance with technology gap. On the contrary, average extension gap was 183 kg/ha, which might be attributed to adoption of improved technology in demonstrations that resulted in higher grain yield than the traditional farmers practices. Finally it may be concluded that in eastern hill region of India, frontline demonstrations of lentil was found more productive, profitable and feasible in local conditions as compared to existing local technology and got success in increasing productivity of lentil during last fifteen years.